Research on the application of colour-changing materials in smart packaging design: Forms, functions, and innovations - Xia, Guanxing; Chuprina, Nataliia (Art and Design, 2025)
The relevance of the research stemmed from the positive role that colour-changing materials played in smart packaging design. It not only addressed consumers’ demand for interactive packaging experiences but also enhanced the additional value of packaging design. The purpose of this study was to explore the current applications and development trends of colour-changing materials in smart packaging design. It was investigated how these materials can be used to convey product information, improve user experience, and increase the functional value of packaging. This study employed the following methods: literary and empirical analysis. Case study analysis and visual analysis methods were applied to examine visual effects. The research systematically analysed how different brands (Anrealage, Disney, Phillips Distilling, Maeil Milk, Leaf Bandage, Warm Me, McDonald’s, Yuan Qi Forest, Coors Light, Naked, Coca-Cola, Lipton, Monster Party) utilised colour-changing materials in their packaging designs and the visual effects achieved. The synergistic innovation space of colour-changing materials in smart packaging design was confirmed. The study revealed that most brands’ smart packaging employed two types of materials: photochromic and thermochromic. These materials exhibited reversible colour changes under external stimuli, which enabled real-time visualisation of product quality, temperature variations, and anti-counterfeiting verification. It generated visual signalling, enhanced brand differentiation, and transformed conventional packaging design. Furthermore, the research also identified a new method that supports customisable colour-changing materials, which provided both theoretical and practical advancements in this field. The practical significance of this study lies in the application of colour-changing materials in smart packaging design, which enhances the entertainment value and interactive function of packaging, and will contribute to the market competitiveness of packaging products and the development of the industry.